The association between neutrophil lymphocyte ratio and perihematomal edema in cerebral hemorrhage: a multicenter retrospective study - Yanwei Liu; Qi Liu; Jun Wei; Shiqiang Yang; Shiqiang Yang (Frontiers in Neurology)
BackgroundPerihematomal edema (PHE) after a brain hemorrhage is an increase in the water content of the brain tissue surrounding the haematoma, which can be observed and measured on imaging. PHE is one of the major secondary brain injuries after a brain hemorrhage and is strongly associated with poor patient prognosis. The relationship between the neutrophil-lymphocyte ratio (NLR) and cerebral oedema after cerebral hemorrhage remains unclear.MethodsData for this study were obtained from a registry database of hospital admissions at two medical institutions covering the population of southwest China. The researchers compared outcomes, including demographics, medical history and lesion characteristics, for all included cases. The primary exposure factor for this study was NLR on admission (NLR1), while NLR measured between 3 and 5 days of treatment (NLR2) was used as a secondary exposure factor for comparison. The study outcome was the degree of PHE after 5–7 days of standardized treatment. The association between NLR and PHE was examined using Restricted cubic spline (RCS) and Logistic regression modeling, and absolute rate differences and risk ratios with 95% confidence intervals were calculated.ResultsA total of 143 patients with confirmed hypertensive cerebral hemorrhage were finally included. Their mean age was 52.8 ± 9.1 years and 53.1% were female. Restricted cubic spline analysis suggested a linear positive correlation between admission NLR and PHE. Logistic regression analysis adjusted for covariates showed that admission NLR was significantly associated with the risk of developing moderate to severe PHE (OR, 1.61 [95% CI, 1.03–2.5]; p = 0.035). In addition, NLR was divided into higher and lower groups according to the median and then analyzed by logistic model regression with multiple covariate adjustment. The results showed that a higher NLR was significantly associated with a higher risk of moderate to severe PHE compared to the lower group (OR, 2.47 [95% CI, 1.59–3.92]; p = 0.021). These results remained stable in subsequent subgroup and sensitivity analyses.ConclusionAdmission NLR was significantly and linearly positively correlated with PHE. In clinical practice, admission NLR can be used as a predictor of potentially moderate to severe PHE. However, further research is needed to explore and explain this due to potential residual confounders.